Transcriptome Analysis Revealed Overlapping and Special Regulatory Roles of RpoN1 and RpoN2 in Motility, Virulence, and Growth of Xanthomonas oryzae pv. oryzae - Yu, Chao; Nguyen, Doan-Phuong; Yang, Fenghuan; Shi, Jia; Wei, Yiming; Tian, Fang; Zhao, Xiuxiang; Chen, Huamin (Frontiers in Microbiology, 2021)
σ54 factor (RpoN) plays a crucial role in bacterial motility, virulence, growth, and other biological functions. In our previous study, two homologous σ54 factors, RpoN1 and RpoN2, were identified in Xanthomonas oryzae pv. oryzae (Xoo), the causative agent of bacterial leaf blight in rice. However, their functional roles, i.e., whether they exert combined or independent effects, remain unknown. In the current study, rpoN1 or rpoN2 deletion in Xoo significantly disrupted bacterial swimming motility, flagellar assembly, and virulence. Transcriptome analysis led to the identification of 127 overlapping differentially expressed genes (DEGs) regulated by both RpoN1 and RpoN2. Furthermore, GO and KEGG classification demonstrated that these DEGs were highly enriched in flagellar assembly, chemotaxis, and c-di-GMP pathways. Interestingly, ropN1 deletion decreased ropN2 transcription, while rpoN2 deletion did not affect ropN1 transcription. No interaction between the rpoN2 promoter and RpoN1 was detected, suggesting that RpoN1 indirectly regulates rpoN2 transcription. In addition, RpoN1-regulated DEGs were specially enriched in ribosome, carbon, and nitrogen metabolism pathways. Besides, bacterial growth was remarkably repressed in ΔrpoN1 but not in ΔrpoN2. Taken together, this study demonstrates the overlapping and unique regulatory roles of RpoN1 and RpoN2 in motility, virulence, growth and provides new insights into the regulatory mechanism of σ54 factors in Xoo.